Montage - Rohdie, Sam, 1939-2015; Manchester University Press (Manchester, UK : Manchester University Press, 2019)
'Montage enters into a dialogue with the cinema, probing and playing with its language of motion and stillness, continuity and discontinuity, constraint and openness, time and duration. Comprised of a series of elegantly-written and intellectually vibrant essays, Sam Rohdie's book carefully expresses his ideas and arguments in a manner free from the complexities of contemporary theory and cultural criticism. As much a book written with the cinema as about it, Montage explores associative and comparative possibilities in the films of directors such as Takeshi Kitano, Jean Renoir, D.W. Griffith, Howard Hawks, Lev Kulsehov, Sergei Eisenstein and Alfred Hitchcock. It offers new and fascinating perspectives on mise en scène, framing, shots, and narrative variation. In combining the sensitive analysis of film forms and structures with an awareness of their historical and artistic relation to other art forms, it also elucidates an appreciation of montage aesthetics that is attentive to the influences of photography, painting and other arts. Montage is a book that will enrich our ways of seeing, understanding, and enjoying the cinema' --Back cover.
Introduction -- Eadwaerd Muybridge -- Takeshi Kitano -- Takeshi Kitano (2) -- Pier Paolo Pasolini -- Lev Kuleshov -- Sergei Eisenstein -- Sergei Eisenstein (2) -- David Wark Griffith -- David Wark Griffith (2) -- David Wark Griffith (3) -- Éric Rohmer -- Alfred Hitchcock -- Samuel Fuller -- Dziga Vertov -- Howard Hawks -- Howard Hawks (2) -- Jean Renoir -- Jean Renoir (2) -- Jacques Rivette -- Michelangelo Antonioni -- Michelangelo Antonioni (2) -- Jacques Rivette (2) -- Alain Resnais -- Alain Resnais (2) -- Étienne-Jules Marey -- Bibliography.
Made available via: manchesterhive.
Includes bibliographical references and index.
In English.
Print version record
JSTOR
Keywords: Motion pictures -- Editing; Motion pictures -- Production and direction; Motion picture producers and directors -- History and criticism; Montage (Cinéma); Cinéma -- Production et réalisation.; Producteurs et réalisateurs de cinéma -- Histoire et critique; The arts; PERFORMING ARTS -- Film -- General; PERFORMING ARTS / Film / General; Motion pictures -- Production and direction; Motion pictures -- Editing; Motion picture producers and directors; The Arts -- Performing arts -- Films, cinema; Electronic books; Criticism, interpretation, etc